Prevalence of job stress and its associated factors among Universiti Putra Malaysia staff - Mukosolu, Okonkwo; Ibrahim, Faisal; Gyanchand Rampal, Lekhraj Rampal; Ibrahim, Nomala (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2015)
Stress in the work place is a global major risk factor to worker’s health, which triggers the workers to be poorly motivated and less productive. Objectives: The objective of the study was to determine the prevalence of job stress and its associated factors among Universiti Putra Malaysia staff. Methods: This is a cross sectional study involving 511 academic and non-academic staff of Universiti Putra Malaysia in Serdang. Probability proportionate to size was used for calculating the required sample size. Results: The overall prevalence of stress was 21.7% (21.0% among male and 23.0% among female). The variables found to be significantly associated with stress were: Job demand, coworker support, depression, anxiety, focus and venting of emotion and self-blame (p<0.05). The findings revealed that UPM staffs are exposed to a range of specific stressors such as work stressor: job demand, lack of social support such as co-worker support and supervisor support, psychological stressors such as depression and anxiety, coping such as focus and venting of emotion and self-blame. Work stressor such as job demand was the main predictor of stress (p value = 0.001). Conclusion: The overall prevalence of job stress was 21.7%. The predictors job stress were job demand, lack of support from co-worker and supervisor, depression, anxiety and use of avoidance focused coping.